Knowledge mapping and management - White, Don 1957- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2002)
This book presents information on knowledge management and mapping in the context of the learning organization, including the design of information technology in Internet-enabled organization forms